The use of oxygenated saline enteral solution in the complex intensive care of severe community-acquired pneumonia caused by COVID-19 - M. V. Bykov; D. V. Chernyshev; Yu. A. Loptev; S. V. Krasnova; N. A. Tsvetkova; Zh. B. Ponezheva; V. G. Akimkin (Лечащий Врач)
COVID-19 is an acute respiratory tract infection caused by SARS-CoV-2 coronavirus. Genetic sequencing of the virus has shown that it belongs to beta-coronaviruses related to the SARS virus. In most cases, COVID-19 has a mild course without complications, but 14–20% of patients develop a severe course that requires hospitalization and oxygen support.The effect of oxygenated saline enteral solution (OSES) in complex intensive care on the possibility of correcting gastrointestinal dysfunction and systemic oxygenation in severe community-acquired pneumonia caused by COVID-19 was determined. Our goal is to capture the attention of specialists to the prevention and treatment of intestinal insufficiency syndrome and enterogenic intoxication due to hypoxic damage to the intestine with the probable translocation of microorganisms in patients with severe respiratory failure developed against the background of community-acquired viral pneumonia COVID-19. The article describes the first experience with the use of OSES in complex intensive care in this category of patients.The results obtained suggest the pathogenetic validity and feasibility of using oxygenated saline enteral solution in the complex intensive care of community-acquired viral pneumonia with COVID-19.The use of OSES, in the authors’ opinion, is of particular scientific and practical interest in the current epidemiological situation and deserves the attention of various specialists, and also requires further in-depth study of the effectiveness of this method in the combination therapy of COVID-19.